The Application of the Crime of Picking Quarrels and Provoking Trouble in Cyberspace in China - Duoran; Daorentuya; Gegen (Studies in Law and Justice, 2023)
In 2013, The Supreme People’s Procuratorate, the Supreme People’s Court issued “about the use of information network defamation criminal cases of applicable law” (hereinafter referred to as “the interpretation”), the judicial interpretation of article 5 on the Internet intimidation, abuse others or trouble, can also establish stir-up-trouble crime. This article in “Interpretation” expands the scope of the crime of picking quarrels and provoking troubles to cyberspace, forming a mode of the crime of picking quarrels and provoking troubles. Although the introduction of the Interpretation has played a positive role in regulating the behavior of picking quarrels and provoking troubles, the threshold of the crime of picking quarrels and provoking troubles is vaguer than the traditional identification of the crime of picking quarrels and provoking troubles, which to some extent leads to the confusion of the crime of picking quarrels and provoking troubles. Therefore, based on the theory and judicial basis of the crime of picking quarrels and provoking troubles, combined with the actual needs of the current cyberspace governance, it is necessary to study the related problems of the crime of picking quarrels and provoking troubles.